MINAT PEDAGANG MUSLIM PASAR TRADISIONAL DI KOTABARU TERHADAP PRODUK BANK SYARIAH - Sintiya Dewi Atmaja Putri; Difi Dahliana (Program Studi Ekonomi Syariah IAI Darul Ulum Kandangan, 2023)
Muslim traders should have high interest in Islamic banking. However, the authors found gaps in the results of previous studies in various regions of Indonesia. Some traders are interested, but some are not interested in Islamic banks. Therefore, this study aims to find out how the interest of Muslim traders in the traditional markets of Kotabaru district, South Kalimantan province, towards Islamic banks. This research is field research with quantitative methods. Data was collected using a questionnaire developed from the AIDA approach (Attention, Interest, Desire, Action). This study involved 100 traders as respondents. The results of this study show that the interest of Muslim traders in Kotabaru traditional markets is in the moderate category, so a more proactive approach and promotion from Islamic banks is needed.